2019
DOI: 10.1021/acsami.9b06866
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Porphyrin-Based Organic Nanoparticles with Remarkable Photothermal Conversion Efficiency for in Vivo Photoacoustic Imaging and Photothermal Therapy

Abstract: Near-infrared (NIR)-absorbing organic nanoparticles (ONPs) are emerging candidates for “one-for-all” theranostic nanomaterials with considerations of safety and formulation in mind. However, facile fabrication methods and improvements in the photothermal conversion efficiency (PCE) and photostability are likely needed before a clinically viable set of candidates emerges. Herein, a new organic compound, [porphyrin–diketopyrrolopyrrole (Por–DPP)] with the donor–acceptor structure was synthesized, where porphyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 54 publications
1
69
0
Order By: Relevance
“…As depicted in Figure 1D, when the concentration of PTM NPs reached 160 μg/mL, the solution temperature rose rapidly to 72.4°C under NIR laser irradiation (808 nm, 1.5 W/cm 2 , 10 min). It is worth noting that PTM NPs also reached effective hyperthermia (45 °C) with the concentration of 40 μg/ mL under the same conditions, demonstrated that PTM The photothermal conversion efficiency of PTM NPs was evaluated to be ~56.9% according to the reported method (Figure S9), 53 which is significantly superior to most previously reported photothermal reagents, including porphyrin (62.5%), 54 phthalocyanine-based nanodots (45.7%), 55 cyanine dyes (26.6%), 56 polypyrrole NPs (45%), 57 dopamine-melanin NPs (40%), 58 Au nanorods (21.0%), 59 MoS 2 nanosheets (24.4%). 60 All these results confirmed that PTM NPs can act as a promising candidate for photothermal therapy.…”
Section: Resultsmentioning
confidence: 61%
“…As depicted in Figure 1D, when the concentration of PTM NPs reached 160 μg/mL, the solution temperature rose rapidly to 72.4°C under NIR laser irradiation (808 nm, 1.5 W/cm 2 , 10 min). It is worth noting that PTM NPs also reached effective hyperthermia (45 °C) with the concentration of 40 μg/ mL under the same conditions, demonstrated that PTM The photothermal conversion efficiency of PTM NPs was evaluated to be ~56.9% according to the reported method (Figure S9), 53 which is significantly superior to most previously reported photothermal reagents, including porphyrin (62.5%), 54 phthalocyanine-based nanodots (45.7%), 55 cyanine dyes (26.6%), 56 polypyrrole NPs (45%), 57 dopamine-melanin NPs (40%), 58 Au nanorods (21.0%), 59 MoS 2 nanosheets (24.4%). 60 All these results confirmed that PTM NPs can act as a promising candidate for photothermal therapy.…”
Section: Resultsmentioning
confidence: 61%
“…Notably, aggregation‐caused thermal release is also effective for semiconductive polymeric materials, which are usually designed by covalent conjugation of donor and acceptor units. Such polymers enable both intramolecular and intermolecular charge transfer, which significantly inhibits emission and, in turn, enhances the photothermal conversion efficiency . For example, Pu and co‐workers developed a semiconducting copolymer poly[(diketopyrrolopyrrole‐ alt ‐cyclopentadithiophene)‐ ran ‐(diketopyrrolopyrrole‐ alt ‐thiadiazoloquinoxaline)] (PDCDT) containing two segments which showed absorption in different NIR windows (Figure b) .…”
Section: Supramolecular Photothermal Effectsmentioning
confidence: 99%
“…12,13 PTN are one key reason for effective PTT. [14][15][16] To achieve high PTT efficiency, PTN with biocompatible, NIR emissive and well photothermal properties are favorable. [17][18][19] Indocyanine Green (ICG) is a clinically relevant contrast agent which is approved by the Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%